Studying the jovian Trojan dust - Elía, Gonzalo Carlos de (2010)
Aims. We analyze the jovian Trojan dust in the L4 swarm. Methods. To do this, we use a modification of the numerical code developed by us and previously applied to the collisional and dynamical evolution of the L4 jovian Trojans. This algorithm considers catastrophic collisions and cratering events, includes a dynamical treatment that takes the stability and instability zones of the L4 jovian swarm into account, and incorporates the effects of the Poynting-Robertson radiation. Results. From this analysis, we infer that the time evolution of the L4 jovian Trojan dust luminosity has the characteristics of a diffusion process, since its current value is fairly insensitive to variations in the initial size distribution. Moreover, our results indicate that the current luminosity of the dust in the L4 jovian swarm ranges from ∼3.2 x 10-8 to 3.4 x 10-8 L⊙. Conclusions. From these estimates, we conclude that the current luminosity of the dust in the L 4 jovian swarm is comparable to the luminosity of the inner Solar System dust, and, at least, one order of magnitude lower than the luminosity of the outer Solar System dust.